The Threshold Level of the Sensor Histidine Kinase KinA Governs Entry into Sporulation in Bacillus subtilis - Eswaramoorthy, Prahathees (American Society for Microbiology (ASM), 2010)
Sporulation in Bacillus subtilis is controlled by a complex gene regulatory circuit that is activated upon nutrient deprivation. The initial process is directed by the phosphorelay, involving the major sporulation histidine kinase (KinA) and two additional phosphotransferases (Spo0F and Spo0B), that activates the master transcription factor Spo0A. Little is known about the initial event and mechanisms that trigger sporulation. Using a strain in which the synthesis of KinA is under the control of an IPTG (isopropyl-β-d-thiogalactopyranoside)-inducible promoter, here we demonstrate that inducing the synthesis of the KinA beyond a certain level leads to the entry of the irreversible process of sporulation irrespective of nutrient availability. Moreover, the engineered cells expressing KinA under a σ(H)-dependent promoter that is similar to but stronger than the endogenous kinA promoter induce sporulation during growth. These cells, which we designated COS (constitutive sporulation) cells, exhibit the morphology and properties of sporulating cells and express sporulation marker genes under nutrient-rich conditions. Thus, we created an engineered strain displaying two cell cycles (growth and sporulation) integrated into one cycle irrespective of culture conditions, while in the wild type, the appropriate cell fate decision is made depending on nutrient availability. These results suggest that the threshold level of the major sporulation kinase acts as a molecular switch to determine cell fate and may rule out the possibility that the activity of KinA is regulated in response to the unknown signal(s).